2005
DOI: 10.1007/bf02287325
|View full text |Cite
|
Sign up to set email alerts
|

Measuring preferences for schizophrenia outcomes with the time tradeoff method

Abstract: Measuring preferences for schizophrenia outcomes facilitates meaningful integration of multiple outcome measures and multiple perspectives on treatment outcomes. The Time Tradeoff (TTO) technique, specifically developed for measuring health state preferences, is used widely in health research, but some evidence suggests that the TTO may work less well with schizophrenia than with other health conditions. This study tested the hypotheses that tailoring the time frame of the standard TTO to the course of schizop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Among the 24 studies that used adapted methods, 20 justified their choice. Five of the studies that used modified TTO and/or SG cited the temporary nature of the HS being assessed [56,58,69,72] and the inappropriateness of classic conventional methods for THS valuation [74] as reasons for this. Brazier et al [66] used a modification of TTO [81], because they felt that the chained approach was likely to generate biased estimates.…”
Section: Justification For Choice Of Methods For Thsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 24 studies that used adapted methods, 20 justified their choice. Five of the studies that used modified TTO and/or SG cited the temporary nature of the HS being assessed [56,58,69,72] and the inappropriateness of classic conventional methods for THS valuation [74] as reasons for this. Brazier et al [66] used a modification of TTO [81], because they felt that the chained approach was likely to generate biased estimates.…”
Section: Justification For Choice Of Methods For Thsmentioning
confidence: 99%
“…Sixteen studies used data collected from respondents in the United States [26,27,39,41,[49][50][51][52][53][54][55][56][57][58][59][60]. Eight studies were conducted in the United Kingdom [61][62][63][64][65][66][67][68], six in the Netherlands [69][70][71][72][73][74], and three in Canada [75][76][77].…”
Section: Summary Of Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of schizophrenia treatment with public policy makers, consumers, families, and providers have shown that respondents value reduction of positive symptoms and improved social functioning over reduction of negative symptoms and EPS (5). Other studies have shown that medication side effects are of greater concern to patients and their families than to clinicians (6)(7)(8)(9)(10). Therefore, our research question was "Which key benefit and risk attributes of second-generation antipsychotics do physicians trade off and consider when balancing formulation and adherence as adherence changes?…”
mentioning
confidence: 97%
“…Previous studies of antipsychotic preference have demonstrated that patients, physicians, and family members collectively place greater importance on productive activity (work or school) compared with positive symptoms or social functioning and place less importance on negative symptoms and side effects (8,9). Medication side effects are of greater concern among patients and their families than among clinicians (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%